Studying the Inflammatory Responses to Amyloid Beta Oligomers in Brain-Specific Pericyte and Endothelial Co-Culture From Human Stem Cells - Marzano, Mark; Chen, Xingchi; Russell, Teal A.; Medina, Angelica; Wang, Zizheng; Hua, Timothy; Zeng, Changchun; Wang, Xueju; Sang, Qing-Xiang; Tang, Hengli; Yun, Yeoheung; Li, Yan (Frontiers in Chemical Engineering, 2022)
Background: Recently, the in vitro blood brain barrier (BBB) models derived from human pluripotent stem cells have been given extensive attention in therapeutics due to the implications it has with the health of the central nervous system. It is essential to create an accurate BBB model in vitro in order to better understand the properties of the BBB and how it can respond to inflammatory stimulation and be passed by targeted or non-targeted cell therapeutics, more specifically extracellular vesicles. Methods: Brain-specific pericytes (iPCs) were differentiated from iPSK3 cells using dual SMAD signaling inhibitors and Wnt activation plus fibroblast growth factor 2 (FGF-2). The derived cells were characterized by immunostaining, flow cytometry and RT-PCR. In parallel, blood vessels organoids were derived using Wnt activation, BMP4, FGF2, VEGF and SB431542. The organoids were replated and treated with retinoic acid to enhance the blood brain barrier (BBB) features in the differentiated brain endothelial cells (iECs). Co-culture was performed for the iPCs and iECs in transwell system and 3-D microfluidics channels. Results: The derived iPCs expressed common markers PDGFRb and NG2, as well as brain-specific genes FOXF2, ABCC9, KCNJ8, and ZIC1. The derived iECs expressed common endothelial cell markers CD31, VE-cadherin, as well as BBB-associated genes BRCP, GLUT-1, PGP, ABCC1, OCLN, SLC2A1. The co-culture of the two cell types responded to the stimulation of amyloid β42 oligomers by the upregulation of expression of TNFa, IL6, NFKB, Casp3, SOD2 and TP53. The co-culture also showed the property of trans-endothelial electrical resistance. The proof-of-concept vascularization strategy was demonstrated in a 3-D microfluidics-based device. Conclusion: The derived iPCs and iECs have brain-specific properties and the co-culture of iPCs and iECs provides an in vitro BBB model that show inflammatory response. This study has significance in establishing micro-physiological systems for neurological disease modeling and drug screening.